Bilateral fungal keratitis with ring infiltrates: a rare scenario - Chaniyara, Manthan Hasmukhbhai (BMJ Case Rep, 2017)
A 12-year-old boy presented to the emergency department with chief complaints of pain, redness, discharge and diminution of vision in both eyes over the previous 20 days. There was no history of preceding trauma, contact lens use, any eye drop usage or ocular surgery. Systemic history was not significant. Presenting uncorrected visual acuity in his right eye was counting fingers at 1 m and 20/200 in the left eye, with accurate projection of rays in both eyes. Slit lamp biomicroscopy showed the presence of bilateral diffuse conjunctival congestion, corneal ring infiltrates and epithelial defect with corneal oedema. Potassium hydroxide wet mount showed the presence of septate fungal hyphae. The patient was treated with topical 5% natamycin and 1% voriconazole over a period of 6 weeks. Best-corrected visual acuity was 20/600 in the right eye and 20/20 in the left eye at 6-month follow-up.